Researching Triads in Home Care: Perceptions of Safety From Home Care Clients, Their Caregivers, and Providers. (May 2014) - Lang, Ariella; Macdonald, Marilyn T.; Storch, Jan; Stevenson, Lynn; Mitchell, Lori; Barber, Tanya; Roach, Sheri; Toon, Lynn; Griffin, Melissa; Easty, Anthony; Curry, Cherie Geering; LaCroix, Hélène; et al.
Home care demand in Canada has more than doubled in recent years. While research related to safety in home care is growing, it lags behind that of patient safety in institutional settings. One of the gaps in the literature is the study of the perceptions of home care triads (clients, their unpaid caregivers, and paid providers). Thus, the objectives of this qualitative study were to describe the safety challenges of home care triads and to further understand the multiple dimensions of safety that contribute to or reduce safety concerns for these triads. Findings indicate that clients, unpaid caregivers, and providers struggle in the home care system. Home care models that are client centered need to be considered to provide seamless, quality, sustainable home care.